Development of a Love-Wave Biosensor Based on an Analytical Model - Frédéric Sarry; Jeremy Bonhomme; Mourad Oudich; Pedro Alberto Segura Chavez; Denis Beyssen; Omar Elmazria; Mohd Khairuddin Md Arshad; Paul G. Charette (Chemosensors, 2022)
The present work deals with the development of a Love-wave biosensor for the diagnosis of the modification of cell viscosity. The relevant device performance such as insertion loss, attenuation, phase velocity, and sensitivity needs to be analysed as a function of the device structure and also regarding the effect of the liquid loading. In this study, we used an analytical model based on the equation of motions for a Love wave propagating in a three-layer structure. We show that the effect of the viscous coupling leads to insertion losses and a phase shift that impact the acoustic ratio. A comparison between experimental and theoretical results showed a good agreement between the behaviours as it was observed for the phase shift vs. the insertion loss with a limited difference in values (3.11/3.09—experimental/simulation for the sensitivity to the viscosity for different insertion losses) due to the assumptions made on the model used.